After liberalization: public-interest services in the utilities - Adrienne Héritier (Max-Planck-Projektgruppe Recht der Gemeinschaftsgüter, 1998)
Public-interest services constitute an essential element of the modern welfare state. The provision of utilities for all at an affordable price have long been regarded as a prerequisite of everyday life generally guaranteed by the state. But in recent years, publicly-owned utilities throughout Europe have come under increasing fire for their poor performance in productive efficiency, identifying consumer demands, and service innovation. As a consequence, and driven by the influence of neo-liberal thought, many public monopolies have been, or are in the course of being, privatized and utility markets of being deregulated. This on-going process spreads across a variety of utilities such as transportation, telecommunications, postal services, and the provision of energy. While some countries, such as Britain, took radical measures early on, others, such as France, have been more hesitant. The experience of early reform measures, instruments and institutional arrangements allow us to tentatively take stock of the situation with regard to the quality of service provision. Moreover, the mixed performance of privatized and deregulated utilities vis-à-vis the public-interest goals traditionally linked to their provision have led to a reform of the early reforms, in so far as deregulation was followed by re-regulation. This gives rise to the following questions: Are the public-service goals of accessibility, security, continuity and affordability in the countries undergoing a reform process still in place? If so, to what extent have they been achieved? If only partially, what are the underlying causes, and what consequences have been drawn in terms of re-regulation? Can utility services be provided under conditions of competition so as to guarantee public-interest goals? In what follows I will start by outlining the pertinent theoretical questions and derive propositions as to the factors accounting for the performance of privatized and deregulated utilities. I will then briefly outline the regulatory structure, goals and performance of the former public monopolies before going on to examine the reformed regulatory structure and its impacts on service provision. Finally, the question is addressed: 'What can we learn from the outcomes of the reform?' The analysis will focus on the liberalization of network-based utilities, that is, rail transport and telecommunications, using the empirical examples of Britain, Germany and France.
Keywords: 340